A multicenter experience with peri-rectal tumors: The risk of local recurrence. Issue 6 (June 2016) - Buchs, N.C.; Gosselink, M.P.; Scarpa, C.R.; Ris, F.; Saiji, E.; Bloemendaal, A.L.A.; van Onkelen, R.S.; Guy, R.J.; Schouten, W.R.; Roche, B.; George, B.D.
Abstract: Background: Peri-rectal tumors are rare and their management is challenging, especially when presenting with local recurrence. The aim of the current study was to report a multicenter series of peri-rectal tumors, focusing on the risk of recurrence. Material and methods: From 1994 to 2014, patients with peri-rectal tumors from three different centers were retrospectively analyzed. Sixty-two patients were identified and divided into two groups; Group 1: patients who presented with local recurrence at follow-up (n = 9, recurrence rate: 14.5%), and Group 2: patients without recurrence (n = 53). Results: In Group 1, there were initially more patients with symptoms of a perineal mass (44.4% vs. 12.2%; p = 0.04), more malignant tumors (55.6% vs. 15.1%; p = 0.02), and larger lesions (+2.6 cm; p = 0.004). Incomplete resection was also more frequent in Group 1 (44.4% vs. 3.8%; p = 0.003). Eight patients with recurrence had further surgery, whilst one patient had radiological recurrence and was treated medically. Among the eight re-resections, five patients remain disease-free; two have had further recurrences and have had palliative treatment, whilst another has had a further resection and remains disease-free. Conclusions: Peri-rectal tumors are uncommon and there is no consensus on best management. Based on this large multicenter series, several risk factors seem to be associated with local recurrence, namely patient- (discovery of a perineal mass), tumor- (malignant and large lesion), and surgery-related (incomplete resection). Clinical follow-up should be adapted according to these factors.